2017
DOI: 10.18632/oncotarget.17982
|View full text |Cite
|
Sign up to set email alerts
|

Increased CCL19 expression is associated with progression in cervical cancer

Abstract: Cervical cancer is the third most common cancer and the fourth leading cause of malignancy related mortality in women worldwide. CCL19 is highly expressed in human cancer cells, and ligand CCL19 binding to CCR7 induces actin polymerization and pseudopodia formation. However, whether or not CCL19 is involved in EMT of human cervical cancer needs further investigation. Using quantitative PCR and western blot analyses, we found that CCL19 is overexpressed in cervical cancer cell lines and tissues. Knockdown of CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…T cells expressing CCR7, in contrast with CD56 bright NK cells, did not increase in the blood of stage IV melanoma patients, suggesting that T cells may overcome the increased CCL19 sera concentration and redistribute to peripheral tissues. The scenario emerging from our study is that melanoma cells and related CSCs may produce CCL19, as described for cervical cancer (41). The increased serum concentration of CCL19 found in stage IV melanoma patients could be explained by the higher disease burden, where an increased number of CSCs actively secrete the chemokine.…”
Section: Discussionmentioning
confidence: 56%
“…T cells expressing CCR7, in contrast with CD56 bright NK cells, did not increase in the blood of stage IV melanoma patients, suggesting that T cells may overcome the increased CCL19 sera concentration and redistribute to peripheral tissues. The scenario emerging from our study is that melanoma cells and related CSCs may produce CCL19, as described for cervical cancer (41). The increased serum concentration of CCL19 found in stage IV melanoma patients could be explained by the higher disease burden, where an increased number of CSCs actively secrete the chemokine.…”
Section: Discussionmentioning
confidence: 56%
“…et al, 2017 ), and it also exhibits transcriptional repression by epigenetic inactivation in specific cervical cancer cell lines, thus it may contribute to the constitutive activation of the Wnt signaling pathway in cervical carcinogenesis ( Lee et al, 2008 ). A large number of studies have demonstrated that chemokines are involved in the progression, migration, and survival of cancers, such as CXCL12 (ENSG00000107562), CCL21 (ENSG00000137077), and especially CCL19 (ENSG00000172724), which is associated with progression of cervical cancer ( Teicher and Fricker, 2010 ; Xiong et al, 2017 ; Zhang et al, 2017 ). Homeobox B13 (HOXB13, ENSG00000159184) is a susceptibility gene for prostate cancer ( Xu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine CC ligand 19 (CCL19), which is also named as macrophage inflammatory protein 3-beta (MIP-3b), mediates various cellular behaviors by binding to CCR7 10 . Recent articles have indicated that the CCL19/CCR7 axis can promote tumor progression 11 , 12 . Nevertheless, some other studies indicated that CCL19 can modulate anti-tumor responses in lung cancer and ovarian cancer 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%